Quality assurance program for Angra 1 licence renewal and long-term operation - YOUSSEF MORGHI; Amir Zacarias Mesquita; Ana Rosa BALIZA MAIA (Brazilian Journal of Radiation Sciences)
In Brazil, according to Cnen standard, a nuclear power plant has authorization to operate for 40 years. Angra 1 commercial operation started in 1985 and it has license to operate until 2024. Eletronuclear aims to extend the operation of the Angra 1 plant from 40 to 60 years. To obtain the license renewal by more than 20 years (long-term operation), Eletronuclear will need to meet the requirements of 10 CFR Part 54, Cnen NT-CGRC-007/18 and NT-CGRC-008/18 (Cnen technical notes). To obtain a license renewal to a long-term operation it is necessary to demonstrate that the plants will operate according to safety requirements, through analysis, testing, aging management, system upgrades, as well as additional inspections. Plant operators and regulators must always ensure that plant safety is maintained and, when it is possible, strengthened during the long-term operation of the plant. One of the documents to obtain a license renewal to a long-term operation is the Quality Assurance Program (QAP). Angra 1 has a QAP according to 10CFR 50 App B and Cnen NN 1.16 for safety related items. However, according to 10 CFR50.34, Nureg-1800 Appendix A.2, Nureg-1801 Appendix A-1 of Nuclear Regulatory Commission (NRC) and NT-CGRC-007/18 and NT-CGRC-008/18 of Cnen, the QAP needs to include the items that are not safety related but are included in the Aging Management. This article will discuss the Angra 1 QAP for the license renewal to a long-term operation according the standards approved by Cnen.